Demand Forecasting Analysis of Clay Mask Production Using Time Series Method at PT. Molhar - Moch. Syahrul Amrullah; Kinanti Resmi Hayati (Nusantara Science and Technology Proceedings)
Forecasting is an attempt to predict future conditions through past data. In life, everything is uncertain, it is difficult to predict precisely. In this case PT. MOLHAR wants to analyze the demand forecasting for CLAY MASK products using the time series method. The purpose of this practicum is to be able to analyze the demand for CLAY MASK using the time series method, namely Moving Average 3, Weighted Moving Average 3, and Single Exponential Smoothing and by calculating errors, namely Mean Square Error (MSE), Standard Error Estimation (SEE), Mean Absolute Percentage Error (MAPE), Mean Absolute Deviation (MAD) which will then choose the most appropriate method and ensure that the method used is good to use. demand for sales of CLAY MASK in the following month is 762 units.